1992
DOI: 10.1016/0006-3223(92)90070-g
|View full text |Cite
|
Sign up to set email alerts
|

Signal-transducing G proteins and antidepressant Drugs: Evidence for modulation of α subunit gene expression in rat brain

Abstract: Signal-transducing G proteins, heterotrimers formed of a, [3, and y subunits, are Psychopharmacologic research has traditionally focused on the ef,~ects of antidepressant drugs on individual neurotransmitters, and a variety of acute biochemical effects have been observed. Paralleling the recognition of the typically weeks-long latency to clinical response studies of antidepressant treatment actions have moved from a focus on disparate acute effects to an interest in possible common chronic, changes. Thus, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 51 publications
2
25
0
1
Order By: Relevance
“…Chronic treatment with TCAs induces an increase in the Go-protein levels in different rat brain regions, such as frontal cortex, midbrain and hypothalamus (Lesch et al 1991;Lesch and Manji 1992). Moreover, Yamamoto et al (1992) reported that several TCAs, including clomipramine, were able to increase, in a PTX-dependent manner, the GTPase activity of Go proteins, purified from bovine brain membranes, indicating the ability of these compounds to directly stimulate Go proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic treatment with TCAs induces an increase in the Go-protein levels in different rat brain regions, such as frontal cortex, midbrain and hypothalamus (Lesch et al 1991;Lesch and Manji 1992). Moreover, Yamamoto et al (1992) reported that several TCAs, including clomipramine, were able to increase, in a PTX-dependent manner, the GTPase activity of Go proteins, purified from bovine brain membranes, indicating the ability of these compounds to directly stimulate Go proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to Gs-proteins, the role of Giproteins in the mechanism of action of antidepressant drugs is more controversial. Chronic treatment with antidepressant drugs has been reported to produce a reduction of Gi ␣ and an increase of the Go ␣ protein levels (Lesch et al 1991;Lesch and Manji 1992;Raap et al 1999) in various regions of rat brain, including neostriatum, hypothalamus, frontal cortex and midbrain. By contrast, no alteration of Gi ␣ and Go ␣ protein and mRNA levels in rat brain (cortex, hippocampus, cerebellum) was observed after chronic treatment with tricyclic antidepressants (TCA) and monoamine oxidase inhibitors (Li et al 1993;Chen and Rasenick 1995;Emamghoreishi et al 1996;Dwivedi and Pandey 1997).…”
mentioning
confidence: 99%
“…99 Otro estudio con PCR convencional muestra que la imipramina y la fluoxetina no tienen efecto sobre la expresión de G αs G αi1/2 , G αo y G αq en la corteza frontal y el hipocampo, pero sí un aumento significativo sólo en G α12 . 101 Desde hace tres décadas se conoce que los antidepresivos provocan la regulación a la baja de los receptores β-adrenérgicos 102 o de otros receptores acoplados a G s (v. gr. 5-HT 4 , 5-HT 6 ).…”
Section: B) Efecto Sobre La Expresión De Las Proteínas Gunclassified
“…These results suggest that imipramine and corticosterone treatments modify neither the number of receptors nor their binding properties but they influence in an opposite manner the signaling cascades downstream the receptor. These modifications are likely to involve changes in the capacity of the receptor to activate G protein and/or changes in G protein expression or phosphorylation [15,50,69]. These data are consistent with the results obtained by other investigators who demonstrated that multiple ECS, lithium and fluoxetine reduced the quantity of mRNA for the a subunit of the Gs protein in the CA1 hippcampal area [48,59], while fluoxetine, imipramine, clomipramine, desimipramine and clorgyline also reduced the protein amount of the a subunit of the Gs [50,49].…”
Section: +mentioning
confidence: 99%